Løver, fugle og slanger - Klæsøe, Iben Skibsted (Hikuin, 2002)
Lions, Snakes and Birds By Iben Skibsted Klæsøe A quite different naturalistic sort of animal ornamentation was introduced at the beginning of the Viking Age compared to the art of the preceding periods. Lions, snakes and birds were introduced. These animals quickly changed from a naturalistic form into stylized creatures. On the trefoil brooches the animal of the so-called Borre Style changed from a symmetrical bear to a snake or a dragon-like monster. All the animals are compared with the Christian symbolic repertoire. The lions used for decoration at the beginning of the Viking Age are known as the symbol of God and as the symbolic token of the Evangelist Mark. Many different birds are known from Christian iconography, e.g. the eagle, pigeon and peacock. They all have different symbolic meanings. These birds are used in the art of the 10th and earlier 11th century. The snake appears in the so-called Jelling Style. This motif is used on the famous little cup from the North mound at Jelling, and on a bronze censor. The use of snakes and birds is compared with the Anglo-Continantal style – the Tassilo- chalice Style – of the second half of the 8th century. When the Tassilo-chalice Style and the Jelling Style appear on male equipment the objects carrying this often very fine decoration are of silver and gold. Both styles combine animal decoration, which is usually pagan, with plant ornaments which symbolises the Christian Tree of Life (seen only on the cup in the Jelling Style). Although not very numerous, the objects with these styles are very widespread and comprise a variety of objects. The styles occur on both profane and sacred objects (e.g. the Jelling Style on the cup and the censor). Moreover, the Tassilo-chalice Style was used on the Continent during a period of conversion. In Scandinavia the Jelling Style is used on objects with the same functions, just 150 years later, in a period when knowledge of Christianity and a Christian population was increasing in Denmark. Perhaps both styles reflected a conflict between paganism and Christianity?